Pengembangan Media Pembelajaran POSTAKU Pada Materi Jenis-Jenis Pekerjaan Siswa Kelas IV SD - Hayati, Nurmala; Hakim, Lukman; Aryaningrum, Kiki (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Based on the problems at SD Negeri 142 Palembang, the lack of use of media in social studies learning makes it difficult for students to understand the material on theme 4 subtheme 1 types of work. This research aims to produce Postaku learning media (Poster My Aspirations) that is valid, practical and has potential effects. The type of research method used is Research and Development (R&D) with the ADDIE model. Based on the needs analysis of student learning outcomes, it is known that students are able to achieve the KKM and are able to understand the material on types of work. The development of Postaku learning media (Poster My Aspirations) in social studies IV learning at SD Negeri 142 Palembang has produced learning media products that have been declared valid by media, material and language experts. The results of the Postaku media research (Poster Aspirations) were declared valid with an average result of 89% with the "very valid" category of student response questionnaires of 91.5% in the one to one test 90.1 in the small group for each test. “very practical” category. The test results obtained by students had an average of 85.2% in the "very effective" category, so it can be concluded that in the research on the development of Postaku (Poster My Aspirations) in class IV social studies learning at SD Negeri 142 Palembang, there is validity, practicality and effectiveness. . Keywords: Media, Postaku (Poster of My Dreams), Social Sciences